Transcranial magnetic stimulation as biomarker of excitability in drug development: A randomized, double‐blind, placebo‐controlled, cross‐over study. Issue 6 (3rd February 2022) - Ruijs, Titia Q.; Heuberger, Jules A. A. C.; de Goede, Annika A.; Ziagkos, Dimitrios; Otto, Marije E.; Doll, Robert J.; van Putten, Michel J. A. M.; Groeneveld, Geert Jan
Abstract : Aims: The purpose of this study was to investigate pharmacodynamic effects of drugs targeting cortical excitability using transcranial magnetic stimulation (TMS) combined with electromyography (EMG) and electroencephalography (EEG) in healthy subjects, to further develop TMS outcomes as biomarkers for proof‐of‐mechanism in early‐phase clinical drug development. Antiepileptic drugs presumably modulate cortical excitability. Therefore, we studied effects of levetiracetam, valproic acid and lorazepam on cortical excitability in a double‐blind, placebo‐controlled, 4‐way cross‐over study. Methods: In 16 healthy male subjects, single‐ and paired‐pulse TMS‐EMG–EEG measurements were performed predose and 1.5, 7 and 24 hours postdose. Treatment effects on motor‐evoked potential, short and long intracortical inhibition and TMS‐evoked potential amplitudes, were analysed using a mixed model ANCOVA and cluster‐based permutation analysis. Results: We show that motor‐evoked potential amplitudes decreased after administration of levetiracetam (estimated difference [ED] −378.4 μV; 95%CI: −644.3, −112.5 μV; P  < .01), valproic acid (ED −268.8 μV; 95%CI: −532.9, −4.6 μV; P  = .047) and lorazepam (ED −330.7 μV; 95%CI: −595.6, −65.8 μV; P  = .02) when compared with placebo. Long intracortical inhibition was enhanced by levetiracetam (ED −60.3%; 95%CI: −87.1%, −33.5%; P  < .001) and lorazepam (ED −68.2%; 95%CI: −94.7%, −41.7%; P  < .001) at a 50‐ms interstimulus interval. Levetiracetam increased TMS‐evoked potential component N45 ( P  = .004) in a central cluster and decreased N100 ( P  < .001) in a contralateral cluster. Conclusion: This study shows that levetiracetam, valproic acid and lorazepam decrease cortical excitability, which can be detected using TMS‐EMG–EEG in healthy subjects. These findings provide support for the use of TMS excitability measures as biomarkers to demonstrate pharmacodynamic effects of drugs that influence cortical excitability.